Data Collection in Street Begging Research in Nigeria: The State of the Art and Associated Challenges - Ojedokun, Usman Adekunle (Journal of Applied And Theoretical Social Sciences, 2022)
Nigeria is among the major countries contending with the social problem of street begging. The pervasiveness of the problem has continually placed it at the front burner of scholarly engagements and intellectual discourse. However, despite the existence of abundant literature on the phenomenon of street begging, the epistemological and methodological issues typically embedded in the process of data elicitation from street beggars in Nigeria are yet to command adequate scholarly attention. Therefore, this article attempted to fill this observed lacuna by focusing on the necessity for data collection on street begging and the major challenges that are associated with data elicitation from street beggars in Nigeria. The paper ascribed the necessity for data collection on street begging to multiple reasons. Language barrier, the fluid nature of street begging, the mobile nature of street beggars, and trust issue are among the major challenges that are associated with data collection on street begging research in Nigeria.